PROGRAM LINIER FUZZY PENUH DENGAN ALGORITMA MULTI OBJECTIVE LINEAR PROGRAMMING - S, Mohammad Ervan; Irawanto, Bambang; ., Sunarsih (MATEMATIKA, 2015)
In the linear programming there is one of the certainty assumptions, where each parameters has been known with certainty, but in this real life, the parameters is often can not be stated with certainty, so that the linear programming developed into fully fuzzy linear programming (FFLP). This paper discusses the problem solving FFLP problem with Multi Objective Linear Programming Algorithm. FFLP problem will be converted to MOLP problem with three objective functions by using a new lexicographic ordering on triangular fuzzy numbers and then it is solved by lexicographic method. The value of the fuzzy optimal solution obtained is used to find the optimal value of fuzzy objective function and then do defuzzification to obtain crisp optimal solutions